English Pronunciation in Suprasegmental Features among Seventh Grade EFL Students at SMPN 4 Banyuwangi - Nuzul Ramadhani Triamudi; Wulan Wangi (Journal of English Language and Education, 2026)
Common problems faced by students in pronunciation include misplaced word stress, unnatural intonation patterns, and incorrect rhythm. This research aims to analyse the suprasegmental features of English pronunciation among seventh-grade EFL students at SMPN 4 Banyuwangi. The scope of the study is limited to suprasegmental aspects of pronunciation, specifically word stress, intonation, and rhythm. The researchers employed a descriptive qualitative research design, involving 31 respondents selected through total sampling. The instrument used in this research was a pronunciation test consisting of six sentences that were required to read aloud by the respondents. The result showed that the students’ average pronunciation score was 64% (categorized as “fair”). It means that the students had a sufficient ability in producing English suprasegmental features, although they still experienced difficulties in applying appropriate word stress, intonation, and rhythm consistently. Therefore, more attention to teaching word stress, intonation, and rhythm is needed to improve students’ pronunciation.